P51 Barriers And Facilitators To Effective Self-management Of Asthma – A Systematic Review And Thematic Synthesis. (10th November 2014) - Kirby, SE; Miles, C; Arden-Close, E; Yardley, L; Bruton, A; Hankins, M; Thomas, DM
Abstract : Introduction and objectives: Self-management is an established approach to controlling asthma, recommended in guidelines. Despite the reported effectiveness of self-management, its promotion, uptake and use among patients, carers, and health-care professionals remain low. We conducted a systematic review and thematic synthesis of qualitative research into self-management in adults, children and adolescents with asthma. Our objective was to identify the perceived barriers and facilitators associated with reduced or improved effectiveness of asthma self-management. Method: Electronic databases (Medline, EMBASE, AMED, CINAHL, and PsycINFO; 1996 – August 2013) and British Thoracic Society guidelines were searched for qualitative literature that explored factors relevant to facilitators and barriers to uptake, adherence, or outcomes of self-management in adults, children and adolescents with asthma. We assessed the methodological strengths of the studies using the Critical Appraisal Skills Programme (CASP) tool for qualitative studies, and conducted a thematic synthesis of included studies. Results: Of the 1532 studies initially identified, 34 papers were included in the review. Thematic synthesis identified 10 overarching themes (Figure 1 ) which suggest that barriers and facilitators of self-management included the perceived quality of the relationship between health-care professionals and patients, the perceived adequacy of education around self-management and medications, and positive and negative beliefs about asthma with regards to self-management and existing interventions. Self-management could also be helped or hindered by the amount and type of social support and perceived ease of access to healthcare. In addition, having a co-morbidity, mood/anxiety problems, and encountering professional barriers within the health care system (such as consultation time and access to lung function testing), are perceived to hinder successful self-management of asthma. Conclusion: Perceived barriers and facilitators occur at the level of individuals with asthma (and carers), health-care professionals, and organisations. These findings contribute to our understanding of why existing self-management interventions may not always be effective, and can be used to inform future study into areas where further intervention may improve the adoption of self-management of asthma. For example, future work could include addressing patient and carer beliefs in educational interventions and decisions involving treatment, or greater use of pharmacist educators, patient advocates, and technological interventions.